Análisis de los ingresos económicos de la Municipalidad Provincial de Maynas, periodo 2017 - 2020 - Flores Romero, Liana Silvia (2022)
The economic income received by the Provincial Municipality of Maynas, are financial resources of vital importance, which are generated through the different activities that it develops, and are necessary for the municipality to be able to finance its public expenses, and to be able to fulfill its public purpose, which is to provide a quality service to the population of its jurisdictión. The present investigation called "Analysis of the economic income of the Provincial Municipality of Maynas, period 2017-2020”, had as a general objective to determine the evolution of the economic income of the Provincial Municipality of Maynas in the period 2017 to 2020. Likewise, the research was of a quantitative type and of a descriptive, non-experimental - cross-sectional design. From the analysis and discussion of the results obtained, it was possible to determine that the economic income received by the municipality presented an evolution with a negative trend for study period.